2006
DOI: 10.1093/ajcn/84.3.505
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory proteins are related to total and abdominal adiposity in a healthy adolescent population: the AVENA Study

Abstract: Total body fat seems to be associated with a chronic low-grade systemic inflammation in apparently healthy adolescents. Central obesity is independently associated with C3 concentrations, which makes this marker especially interesting for further studies of obesity-related diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(87 citation statements)
references
References 42 publications
6
78
0
3
Order By: Relevance
“…The correlations found between circulating concentrations of C3 and tricipital ST, sum of STs, BMI and body fat mass as well as the associations between serum C3 and BMI, waist circumference, waist-to-height ratio and body fat (Table 3) reveal that C3 is in some way related with several adiposity markers. These findings are in accordance with previous studies reporting the association between C3 and several adiposity measurements in healthy adolescents (Warnberg et al, 2006), obese adults (Gabrielsson et al, 2003) and type 2 diabetic subjects (Kriketos et al, 2004). Anthropometrical measurements, such as BMI (Halkes et al, 2001;Ylitalo et al, 2001;Onat et al, 2005), waist circumference (Halkes et al, 2001;Onat et al, 2005) and waist-to-hip ratio (Ylitalo et al, 2001), have been considered predictors of high C3 concentrations and have been related with higher expression in visceral than in subcutaneous white adipose tissue (Gabrielsson et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The correlations found between circulating concentrations of C3 and tricipital ST, sum of STs, BMI and body fat mass as well as the associations between serum C3 and BMI, waist circumference, waist-to-height ratio and body fat (Table 3) reveal that C3 is in some way related with several adiposity markers. These findings are in accordance with previous studies reporting the association between C3 and several adiposity measurements in healthy adolescents (Warnberg et al, 2006), obese adults (Gabrielsson et al, 2003) and type 2 diabetic subjects (Kriketos et al, 2004). Anthropometrical measurements, such as BMI (Halkes et al, 2001;Ylitalo et al, 2001;Onat et al, 2005), waist circumference (Halkes et al, 2001;Onat et al, 2005) and waist-to-hip ratio (Ylitalo et al, 2001), have been considered predictors of high C3 concentrations and have been related with higher expression in visceral than in subcutaneous white adipose tissue (Gabrielsson et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Body mass index (BMI) was calculated according to body weight divided by squared height (kg/m 2 ). Skinfold thicknesses (STs) were measured at the right side to the nearest 0.2 mm by means of a Holtain skinfold caliper (Holtain, Crymych, UK) at the triceps, the biceps, subscapular and suprailiac (Warnberg et al, 2006). Waist and hip circumferences were measured with an inelastic tape to the nearest 1 mm.…”
Section: Anthropometry and Body Composition Measurementsmentioning
confidence: 99%
“…53 The finding that low-grade inflammation was significantly associated with simple anthropometric measurements is in agreement with the results from a population sample of Spanish adolescents. 3,4 However, it is noteworthy that inflammatory markers were not associated with the measures of central fatness (waist circumference, waist-to-hip ratio and waist-to-height ratio) once a measure of general fatness (BMI or skinfold thickness) was also entered in the model. Therefore, the detrimental effect of central obesity on lowgrade inflammation may be somehow mediated by general fatness in non-overweight children.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have shown that a state of low-grade inflammation is associated with adiposity in children and adolescents, [3][4][5][6] as it has been shown in adults. 7 Low-grade inflammation is associated with anthropometric measures such as body mass index (BMI) and waist circumference in adolescents, 3,4 but data on children are sparse. Less is known about the association of low-grade inflammation with cardiovascular fitness (CVF) in prepubertal children.…”
Section: Introductionmentioning
confidence: 87%
“…Several studies with children and adolescents have demonstrated a significant association between cardiovascular risk factors and waist circumference. [23][24][25][26][27][28][29] Chronic diseases, including obesity and associated comorbidities (dyslipidemia, diabetes, hypertension, among others) have caused important harmful effects in the general population in physical, emotional, and economic terms. Thus, early identification of individuals at risk for these diseases would have great impact on the improvement of the current health situation worldwide.…”
Section: Discussionmentioning
confidence: 99%